PENGARUH UKURAN PERUSAHAAN DAN KOMITE AUDIT TERHADAP KUALITAS AUDIT: Pada Perusahaan Industrial goods Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2021-2023 - Cahyaningtyas, Nur; Subkhan, Muhamad; Muslim, Ade (Brainy: Jurnal Riset Mahasiswa, 2025)
This study aims to analyze the influence of company size and audit committee size on audit quality in industrial goods companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The method used is a quantitative approach with multiple linear regression analysis. Company size is measured using the natural logarithm of total assets, while the audit committee is measured by the number of its members. Audit quality is proxied by the value of discretionary accruals. The sample consists of 31 companies that have consistently reported financial results for three consecutive years. The results show that the audit committee has a significant positive effect on audit quality, while company size has a significant negative effect on audit quality. The regression model demonstrates very high predictive ability, with an adjusted R² value of 0.985. These findings indicate that a strong internal oversight structure through an audit committee can improve audit quality, while operational complexity in large companies can potentially reduce audit quality.